2011
DOI: 10.1109/tbme.2010.2093896
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Brain Shift Compensation: Accounting for Dural Septa

Abstract: Biomechanical models that describe soft tissue deformation provide a relatively inexpensive way to correct registration errors in image-guided neurosurgical systems caused by nonrigid brain shift. Quantifying the factors that cause this deformation to sufficient precision is a challenging task. To circumvent this difficulty, atlas-based methods have been developed recently that allow for uncertainty, yet still capture the first-order effects associated with deformation. The inverse solution is driven by sparse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 32 publications
2
76
0
Order By: Relevance
“…This is not to say that swelling is not useful in a compensation approach; but rather, thankfully in our work, the incorporation of swelling conditions for use in correction has been found to be quite limited (e.g., in Ref. 13, swelling solutions only influenced about 10% of reconstructed deformations). Nevertheless, the results in Table 7 are promising.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This is not to say that swelling is not useful in a compensation approach; but rather, thankfully in our work, the incorporation of swelling conditions for use in correction has been found to be quite limited (e.g., in Ref. 13, swelling solutions only influenced about 10% of reconstructed deformations). Nevertheless, the results in Table 7 are promising.…”
Section: Discussionmentioning
confidence: 76%
“…These approaches use data from intraoperative microscopes, 8,9 laser range scanners, 10,11 and conoscopic holography devices 12 in conjunction with advanced modelbased image-to-physical registration approaches to compensate for deformations. Furthermore, while intraoperative imaging modalities, such as iMR and iCT, are quite compelling, workflow friendly, and inexpensive solutions using sparse data are certainly attractive; and there have been a variety of approaches 11,[13][14][15] in this direction. We should note that while conventional IGNS essentially only requires that preoperative images be available to the neurosurgeon, these more advanced sparse-data-driven image-to-physical approaches can require significantly more preoperative processing.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that the surface of the brain is deformed by up to 20 mm after the skull is opened during neurosurgery, which could lead to substantial error in commercial image-guided surgery systems [31].…”
Section: Resultsmentioning
confidence: 99%
“…The law determines the tissue behaviour, but there is no consensus about a constitutive equation unifying all the applications, such as simulating deformation during a car crash or a neurosurgery. Brain deformation models have been widely used for training systems, registration of medical images [10], or compensating brain shift [4], but not for the preoperative planning of a surgery.…”
Section: Related Workmentioning
confidence: 99%
“…Due to the impossibility to predict CSF loss, [4] precomputed different brain deformations for possible input parameters, but the goal was to update the different structures position during the surgery which is not our case.…”
Section: Related Workmentioning
confidence: 99%